Analisis Konseptual Peran Uang dalam Menunjang Pertumbuhan Ekonomi: Perspektif Ekonomi Konvensional dan Syariah - Hamam Misbahkhuzein; Nur Wulan Ramdhaniah; Firla Azizah; Gama Pratama (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study seeks to conceptually examine the role of money in fostering economic growth from two different perspectives: conventional economics and Islamic economics. Money functions as a core element within the economic system, serving not only as a medium of exchange, a unit of account, and a store of value but also as a central driver of economic activity. In conventional economics, the role of money is closely linked to monetary policy, interest rate mechanisms, and market dynamics that influence investment, consumption, and inflation. Maintaining monetary stability is viewed as a key factor in achieving macroeconomic equilibrium and supporting national growth. Conversely, Islamic economics perceives money not as a tradable commodity for profit but as a trust (amanah) that should be directed toward productive and just economic activities. The Islamic system prohibits usury (riba), speculation (gharar), and uncertainty, while emphasizing the integration of the monetary and real sectors. In this framework, money serves as a means of equitable wealth distribution through mechanisms such as profit-sharing, zakat, waqf, and other Islamic financial instruments designed to promote social justice and economic fairness. This research adopts a qualitative descriptive approach using the library research method. Data were drawn from academic sources, including economic textbooks, peer-reviewed journals, and official reports issued by financial institutions. The findings suggest that sustainable economic growth can only be achieved through a balanced relationship between market efficiency and social justice. Integrating the rational principles of conventional economics with the ethical and moral foundations of Islamic economics can contribute to the creation of a more inclusive, stable, and sustainable economic system. Ultimately, this study is expected to enrich theoretical discourse in the field of monetary economics and enhance understanding of the role of money in developing a fair and equitable economy. Moreover, it serves as a valuable reference for formulating Islamic monetary policies aligned with national development goals and the principles of maqashid al-shariah